Implementasi Budaya Organisasi dalam Meningkatkan Produktivitas Kerja di Bank Muamalat Kantor Cabang Denpasar - Nur Azizah; Ely Mansur; Sahrial Sahrial (Nirta Learning Centre, 2023)
The objectives of this research are: 1). To find out the implementation of organizational culture in increasing work productivity at Bank Muamalat Denpasar Branch Office. 2). To find out how each employee increases work productivity at Bank Muamalat Denpasar Branch Office? The research methodology used is descriptive qualitative research using triangulation in testing credibility. The informants in this study were 6 employees who worked at Bank Muamalat Denpasar Branch Office. As well as data collection techniques in the form of: interviews, documentation and observation. Based on the results of the research, Bank Muamalat Denpasar Branch Office has implemented ideal corporate culture values properly and correctly. Where the organizational culture is applied as motivation for each employee to be more disciplined and have character in the application of organizational culture when carrying out their duties. The application of organizational culture can increase the work productivity of employees which can be seen from the achievements of the company. So that the organizational culture applied so far has been running well and in accordance with sharia principles.